ADHD and Giftedness and the Role of ICTs - Batziaka, Elektra; Galanopoulou, Demetra; Papadogiannis, Ioannis; Papapetrou, Marouso; Drigas, Athanasios (Technium Education and Humanities, 2022)
The focus of this paper is to take a bibliographical look at the existing research concerning students who are considered to be twice exceptional. The specific aim is to find and analyze the most prevalent data available up to the present time of this writing regarding children who possess characteristics on both sides of the learning spectrum, namely students who are regarded as charismatic or gifted, but have also been diagnosed with ADHD. This paper attempts to find methods to aid in the recognition of the characteristics of these students, try to offer different possibilities regarding schemes and techniques in the way of diagnosis. Finally, certain approaches to successful treatment will also be suggested.